Role of decompressive craniectomy in the management of traumatic brain injury - A meta-analysis of randomized controlled trials - Qiang Zhang; Yuhuan Li; Xiaozan Chang (Annals of Indian Academy of Neurology, 2023)
Background: Traumatic brain injury (TBI) is a serious medical condition that often leads to significant morbidity and mortality. Decompressive craniectomy (DC) is now widely recognized as a primary or secondary treatment option for managing intracranial pressure (ICP) in patients with severe TBI. However, there is a lack of clarity in reviews regarding the impact of DC on TBI outcomes. Objectives: The aim of this study is to evaluate the effectiveness of DC in terms of overall mortality and long-term prognosis among patients with TBI. Materials and Methods: We conducted a systematic search of four common databases to include all parallel-arm randomized controlled trials (RCTs). We selected studies that reported outcomes for TBI cases, with DC as a treatment option. The outcomes examined included reduction in mortality, ICP levels, and the proportion of patients with a Glasgow Outcome Scale score >4. Results: Our review finally included eight RCTs [n = 1458, with 749 and 709 patients in the DC and control groups, respectively]. The weighted mean difference for ICP was estimated at -4.01 (95% Confidence interval [CI]: -5.31–-2.71), indicating a statistically significant reduction in ICP levels in the DC group compared to the control group. The pooled risk ratio was 0.67 (95% CI: 0.51–0.89), suggesting a statistically significant 31% decrease in mortality levels in the DC group. Subgroup and sensitivity analyzes were also conducted to address heterogeneity. Discussion and Conclusion: In conclusion, based on our meta-analysis, we find that DC can be considered a crucial surgical intervention for reducing mortality among patients with TBI when compared to control groups.